2019
DOI: 10.1007/s13753-019-00225-1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Coordination: Understanding Intergovernmental Friction During Disasters

Abstract: While idealized crisis response involves smooth coordination between relevant actors, friction between levels of government and between the state and civil society in responding to catastrophe may be more common. This article builds a theory of cross-level friction during and after crisis by analyzing the conditions when discord is most likely. With a medium-N dataset (N = 18) of disaster responses from, among other countries, Chile, Haiti, Japan, North America, the Philippines, and Somalia, I carry out quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The assumption that goal alignment improves emergency and disaster response management, and that goal alignment interventions therefore become implemented in national frameworks, seemed reasonable, given some of the current research (Narayanan and Raman 2004;Aldrich 2019). However, our results suggest that this hypothesis could be wrong, which in turn points to other strands of literature (Rosenthal et al 1991).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The assumption that goal alignment improves emergency and disaster response management, and that goal alignment interventions therefore become implemented in national frameworks, seemed reasonable, given some of the current research (Narayanan and Raman 2004;Aldrich 2019). However, our results suggest that this hypothesis could be wrong, which in turn points to other strands of literature (Rosenthal et al 1991).…”
Section: Discussionmentioning
confidence: 54%
“…Both direction and coordination are tightly linked to goals, because without goals, response efforts lack purpose. In a multiorganizational response operation where interand intraorganizational goals coexist, goal alignment is expected to improve outcomes (Aldrich 2019). In that case, efforts must be made not only to articulate goals, but also to harmonize them and address potential conflicts.…”
Section: Using Experiments To Support the Development Of Design Knowlmentioning
confidence: 99%
“…Although no universal list of stakeholders exists, the literature dealing with civil security governance typically addresses the state at the national but also low-er levels of administration (Wolensky and Wolensky 1990;Krahmann 2003;Field 2012;Zurita et al 2015;Bae et al 2016;Lane and Hesselman 2017); civil society organizations (CSOs) (Coppola 2006;Roberts 2010;Joachim and Dembinski 2011;Zurita et al 2015); and the private (for-profi t) sector (Lethbridge 2009;Roberts 2010;Tierney 2012;Zurita et al 2015). A large body of the literature also stresses the active engagement of the military forces as a distinct actor (Wentz 2006;Coppola 2006;Roberts 2010;Tierney 2012;Zurita et al 2015;Bae et al 2016) and the role of individual citizens as active participants in disaster preparedness and mitigation (Zhang and Kumaraswamy 2012;Wehn et al 2015;Zurita et al 2015;Aldrich 2019;OECD 2017;Lane and Hesselman 2017). Finally, at the international level, the role of transboundary assistance and coordinated international eff ort is stressed as an important element of the governance framework (Coppola 2006;Gopalakrishnan and Okada 2007;Roberts 2010;Ha 2015;Driessen et al 2016;OECD 2017;Lane and Hesselman 2017).…”
Section: Security Governance As a Framework For Analysismentioning
confidence: 99%
“…Focusing on effectiveness, a comparative study among European national security systems undertaken by Kuipers et al (2015) touched upon diff erent analytical dimensions, such as perceptions of the role of government, procedures, and quality in terms of absence of controversies; yet the stakeholder involvement was not the focus of the study. Another large comparative study by Aldrich (2019) compared the level of governance in disaster responses in eighteen countries in the Americas, Asia, and East Africa and showed that democratic societies fi nd collaboration of diff erent stakeholders easier and value civil society and its voluntary organizations as active participants.…”
Section: Stakeholder Involvement In Civil Security Systemsmentioning
confidence: 99%
See 1 more Smart Citation